Deletion of glycine transporter 1 (GlyT1) in forebrain neurons facilitates reversal learning: Enhanced cognitive adaptability? - Singer, Philipp (2009)
Local availability of glycine near N-methyl-d-aspartate receptors (NMDARs) is partly regulated by neuronal glycine transporter 1 (GlyT1), which can therefore modulate NMDAR function because binding to the glycine site of the NMDAR is necessary for channel activation. Disrupting GlyT1 in forebrain neurons has been shown to enhance Pavlovian conditioning and object recognition memory. Here, we reported that the same genetic manipulation facilitated reversal learning in the water maze test of reference memory, but did not lead to any clear improvement in a working memory version of the water maze test. Facilitation in a non-spatial discrimination reversal task conducted on a T-maze was also observed, supporting the conclusion that forebrain neuronal GlyT1 may modulate the flexibility in (new) learning and relevant mnemonic functions. One possibility is that these phenotypes may reflect reduced susceptibility to certain forms of proactive interference. This may be relevant for the suggested clinical application of GlyT1 inhibitors in the treatment of cognitive deficits, including schizophrenia, which is characterized by cognitive inflexibility in addition to the positive symptoms of the disease.